2016
DOI: 10.1038/srep30584
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome landscape of Synechococcus elongatus PCC 7942 for nitrogen starvation responses using RNA-seq

Abstract: The development of high-throughput technology using RNA-seq has allowed understanding of cellular mechanisms and regulations of bacterial transcription. In addition, transcriptome analysis with RNA-seq has been used to accelerate strain improvement through systems metabolic engineering. Synechococcus elongatus PCC 7942, a photosynthetic bacterium, has remarkable potential for biochemical and biofuel production due to photoautotrophic cell growth and direct CO2 conversion. Here, we performed a transcriptome ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Based on re-analysis of published transcriptomic data (Table S2 from [ 49 ] and Table S1 from [ 50 ]), the transcript level of Synpcc7942_0905 was found to be most abundant among all protein-encoding genes of S. elongatus PCC 7942 under normal culture conditions (30 °C, 100 µmol photons/m 2 /s, CO 2 aeration) and significantly changed by the tested treatments. These transcriptional analyses showed that Synpcc7942_0905 is also a highly expressed and sensitive gene to environmental changes, similar to its homolog in S. elongatus UTEX 2973.…”
Section: Resultsmentioning
confidence: 99%
“…Based on re-analysis of published transcriptomic data (Table S2 from [ 49 ] and Table S1 from [ 50 ]), the transcript level of Synpcc7942_0905 was found to be most abundant among all protein-encoding genes of S. elongatus PCC 7942 under normal culture conditions (30 °C, 100 µmol photons/m 2 /s, CO 2 aeration) and significantly changed by the tested treatments. These transcriptional analyses showed that Synpcc7942_0905 is also a highly expressed and sensitive gene to environmental changes, similar to its homolog in S. elongatus UTEX 2973.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the cells rapidly adjust gene expression to various nutritional limitations (Krasikov et al, 2012;Ludwig and Bryant, 2012;Choi et al, 2016). In nitrogen-starved cells, these processes no longer serve as a major sink for products of this electron transfer chain and, thus, it is crucial to adjust the photosynthetic apparatus to the metabolic status of the cell to prevent possible damage associated with over reduction of the photosynthetic electron carriers.…”
Section: Immediate Response Of the Photosynthetic Apparatusmentioning
confidence: 99%
“…In nitrogen-starved cells, these processes no longer serve as a major sink for products of this electron transfer chain and, thus, it is crucial to adjust the photosynthetic apparatus to the metabolic status of the cell to prevent possible damage associated with over reduction of the photosynthetic electron carriers. Accordingly, the cells rapidly adjust gene expression to various nutritional limitations (Krasikov et al, 2012;Ludwig and Bryant, 2012;Choi et al, 2016).…”
Section: Immediate Response Of the Photosynthetic Apparatusmentioning
confidence: 99%
“…The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment of DEGs ( Figure 3 c and Supplementary Table S4 ) showed that nine metabolic pathways were significantly affected by phosphate starvation, of which the three most enriched were ABC transporters, nitrogen metabolism, and cysteine and methionine metabolism. Similar responses were commonly implicated when organisms were exposed to adverse conditions [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 61%